Temporary Balloon Occlusion of the Common Hepatic Artery for Yttrium-90 Glass Microspheres Administration in a Patient with Hepatocellular Cancer and Renal Insufficiency. (27th April 2013) - Smith, Justin; Murthy, Ravi; Lahoti, Amit; Odisio, Bruno; Avritscher, Rony; Chasen, Beth; Mahvash, Armeen
Abstract : The most severe complication of yttrium-90 therapy is gastrointestinal ulceration caused by extrahepatic dispersion of microspheres. Standard pretreatment planning requires extensive angiographic evaluation of the hepatic circulation and embolization of hepatoenteric collaterals; however, in patients with severe renal insufficiency, this evaluation may lead to acute renal failure. In order to minimize iodinated contrast utilization in a patient with preexisting severe renal insufficiency, the authors describe the use of a balloon catheter for temporary occlusion of the common hepatic artery to induce transient redirection of flow of the hepatoenteric arteries towards the liver, in lieu of conventional coil embolization.